Give an Envelope for the Boss/Give a Brown Envelope for the Boss- On the Semantics and Characteristics of the Metaphors for Bribe Across Cultures: Focus on Cameroon and Nigeria - Lozzi Martial Meutem Kamtchueng (National Research University Higher School of Economics, 2017)
This paper sets out to study in a comparative perspective the semantics and the characteristics of the metaphors for bribe used by Cameroonians and Nigerians and discuss the factors which can account for the choice of these metaphors. The data for the study were collected from participant observation, novels, interviews, scientific papers and online sources and the work is discussed from the vantage point of functional grammar and cognitive linguistics. The findings of the study reveal that in order to lessen the appalling nature of the act of asking for bribes, avoid sounding ridiculous and render incomprehensible the message of asking for bribe from people who are not familiar with it, these language users utilize various types of metaphors (object metaphors, anthropomorphic metaphors, vegetative metaphors as well as zoomorphic metaphors). These metaphors display some similarities (which can be accounted for by the geographical proximity between the two countries) and differences: both utilize almost the same types of metaphors and to a lesser extent the same lexical items to refer to bribe but in different proportions (object metaphors, anthropomorphic metaphors, vegetative metaphors as well as zoomorphic metaphors). Furthermore, it is found that the values conveyed by these metaphors fall under the domains of foodstuff and drinks, fauna, human beings and body parts, mailing and transportation as well as abstract realities. Also, some of these metaphors can be characterized as being meliorative, pejorative, vindictive and kinesthetic. Moreover, it is found that cultural, social and economic factors can provide insights to the understanding of the choice of the values used to refer to bribe by these language users. In addition, the values used to represent bribes in these countries are a depiction of their multilingual complex nature.